DESCRIPTION STRESS LEVEL, EMOTIONAL EATING AND PHYSICAL ACTIVITIES ON FINAL YEAR MEDICAL STUDENTS OF UDAYANA UNIVERSITY WHO ARE ON WORKING ON A THESIS - Dhumaranang, Hyangayu Dedari; Weta, I Wayan; Pinatih, Gde Ngurah Indraguna; Pradnyaparamita, Dyah (E-Jurnal Medika Udayana, 2023)
Medical students in their final year are faced with the obligation to do a thesis, including medical students. This obligation is a challenge for students and can certainly affect the psychological and physical health of students. Coping mechanisms to deal with stressful events that each individual carries out are different. This research was conducted to determine the description of stress, emotional eating, and physical activity of Udayana University medical students working on a thesis. The data were collected using the Depression, Anxiety and Stress Scale (DASS-14), DEBQ-13, and IPAQ- Short form questionnaires.  The data obtained are, students who are in the nomal stress category are 43 respondents (41,7%), those who experience mild stress was 17 respondents (16.5%), moderate stress was 24 respondents (23.3%), severe stress was as many as 12 respondents (11.7%) and very heavy stress category as many as seven respondents (6.8%). Students who experience emotional eating are 52 respondents (50.5%). The level of physical activity in the light category was 36 respondents (35.0%), the medium category was 50 respondents (48.5%), and the high category was 17 respondents (16.5%).